2000
DOI: 10.1097/00002826-200005000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Abuse Liability of Modafinil and Other Drugs for Excessive Daytime Sleepiness Associated with Narcolepsy

Abstract: Psychostimulants have been used routinely for the treatment of the disabling daytime sleepiness associated with narcolepsy. However, the perceived and real potential for abuse of amphetamine and amphetaminelike stimulants prompted a search for new wake-promoting compounds with lower dependency and abuse liabilities. Modafinil is a novel wake-promoting agent with a mechanism of action that differs markedly from that of amphetamine and amphetamine-like stimulants. In controlled clinical trials, modafinil has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(66 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…Studies in healthy volunteers, cocaine users and ADHD patients have found fewer side effects than placebo and little evidence of dependence [106]. Use by injection or smoking is limited by the relative insolubility of modafinil and its instability at high temperatures [107]. Consistent with biochemical data, human laboratory studies comparing discriminative stimuli, subject-rated effects and cardiovascular effects concluded that modafinil did not produce cocaine-like responses in subjects with cocaine use histories [107,108].…”
Section: Modafinil and Glutamate Agonismmentioning
confidence: 99%
“…Studies in healthy volunteers, cocaine users and ADHD patients have found fewer side effects than placebo and little evidence of dependence [106]. Use by injection or smoking is limited by the relative insolubility of modafinil and its instability at high temperatures [107]. Consistent with biochemical data, human laboratory studies comparing discriminative stimuli, subject-rated effects and cardiovascular effects concluded that modafinil did not produce cocaine-like responses in subjects with cocaine use histories [107,108].…”
Section: Modafinil and Glutamate Agonismmentioning
confidence: 99%
“…Recently, ( ± )-MOD has been clinically investigated for the treatment of cocaine and methamphetamine addiction. As ( ± )-MOD is a mild psychostimulant and a dopamine transporter (DAT) inhibitor, but with no reported abuse liability (Jasinski and Kovacevic-Ristanovic, 2000;Myrick et al, 2004), it has been suggested as useful for the treatment of psychostimulant dependence. Camacho and Stein (2002) first reported that ( ± )-MOD was effective in treatment of amphetamine dependence in a patient with comorbid social phobia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has recently been reported that patients with baseline cocaine withdrawal (Sofuoglu et al, 2003), and abstinence-related depression and irritability (Newton et al, 2003), report enhanced euphoria after cocaine administration under controlled conditions, suggesting that the reversal of cocaine withdrawal might be clinically advantageous. Modafinil is a reasonable medication for cocaine-dependent individuals because it has low abuse potential (Jasinski, 2000;Jasinski and Kovacevic-Ristanovic, 2000;Rush et al, 2002a, b), neurochemical effects that differ markedly from those of psychostimulants (Lin et al, 1996;Ferraro et al, 1997), and good tolerability (Becker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%